Conceptual Model of Information Technology Management for Smart Cities: SmarTICity (2019)
This article presents a proposal of conceptual model for public administrations that allows analyzing the level of IT management capacity as an enabler of smart cities from a multidimensional and dynamic approach taking into account technological, institutional and innovation aspects. The model includes five domains (e-government strategy, Public Innovation, Data Management, IT Services and Infrastructure) that are described in terms of key domain areas, objectives and questions. The model was conceptually validated with four IT offices in Colombia and a pilot test was developed in the Atlantic department. A profile of information technology management capabilities was obtained from public data of the Ministry of ICT in Colombia. Copyright © 2019, IGI Global.